2010 2nd International Conference on Chemical, Biological and Environmental Engineering 2010
DOI: 10.1109/icbee.2010.5650921
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical oxidation of phenol and chlorophenol by UV/H<inf>2</inf>O<inf>2</inf>/TiO<inf>2</inf> process: A kinetic study

Abstract: In the present work, the photochemical oxidation of phenol and chlorophenol aqueous solutions in a batch recycle photochemical reactor using ultraviolet irradiation, hydrogen peroxide and Ti02 (as photocatalyst) was studied. The study showed that the combined treatment process was the most effective process under acidic conditions and showed a higher rate of degradation of phenol and chlorophenol at a very short radiation time. The reaction was found to follow the first order kinetics and was influenced by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
(8 reference statements)
2
9
0
Order By: Relevance
“…Using 2.0e45.0 mM H 2 O 2 significantly increases the removal efficiency. These results are similar to previous reports (Barakat et al, 2005;Dixit et al, 2010;Ghaly et al, 2001;Shen et al, 1995). When the solution contains 2.0 mM H 2 O 2 , the degradation is Fig.…”
Section: Effect Of the H 2 O 2 Concentration On P-cp Degradationsupporting
confidence: 94%
See 1 more Smart Citation
“…Using 2.0e45.0 mM H 2 O 2 significantly increases the removal efficiency. These results are similar to previous reports (Barakat et al, 2005;Dixit et al, 2010;Ghaly et al, 2001;Shen et al, 1995). When the solution contains 2.0 mM H 2 O 2 , the degradation is Fig.…”
Section: Effect Of the H 2 O 2 Concentration On P-cp Degradationsupporting
confidence: 94%
“…Previous studies have also indicated that excess catalyst will decrease the light penetration via the shielding effect of the suspended particles (Burns et al, 2002;Chiou et al, 2008b;Dixit et al, 2010;Neppolian et al, 2007;Sobczynski et al, 2004). However, compared to the other doses of TiO 2 , 1.0 g/L promotes a high removal of p-CP (79%).…”
Section: Effect Of Tio 2 Dose On P-cp Degradationmentioning
confidence: 87%
“…They detected phenol degradation after nearly 3 h. Dixit and his group [68] studied the photochemical oxidation of phenol and p-chlorophenol by combined process of UV/H 2 O 2 /TiO 2 and achieved a maximum of 74.6 and 79.8 % degradation for phenol and pchlorophenol, respectively. In this work, higher degradation rates were measured for the different phenolic compounds using simulated sunlight.…”
Section: Photocatalytic Reaction Of Phenolic Compounds Under Uv Illummentioning
confidence: 97%
“…Catalytic and photocatalytic oxidation are examples of the AOP techniques. [7][8][9][10][11][12][13][14][15] Even though the thermal catalytic oxidation of phenol provides milder reaction conditions than the non-catalytic process, reactions conducted under more ambient conditions would be more desired. Photocatalytic oxidation reaction would be one of the best technologies that can solve the problem since it can be conducted at around room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was reported that TiO 2 was able to mineralise phenol under UV light irradiation. [9][10][11] However, since sunlight only consists of 5% UV light region and more than 40% visible light region, the development of heterogeneous photocatalysis applicable under visible light irradiation is highly needed. Recently, many efforts have been put into the design of visible light-active photocatalysts for organic pollutant removal.…”
Section: Introductionmentioning
confidence: 99%